Hunting out the autophagic problem in Huntington disease. Issue 12 (2nd December 2022) - Pircs, Karolina; Barker, Roger A.; Jakobsson, Johan
ABSTRACT: Huntington disease is an inherited, progressive, incurable neurodegenerative disorder that primarily affects cells in the brain. Although the genetic basis for this condition has been known for nearly 30 years, how this causes disease is still unresolved. Of late there has been increasing evidence suggesting that dysfunction in macroautophagic/autophagic pathways may contribute to cellular dysfunction and death. In our recent work we highlight more precisely how and where this problem might arise in this pathway using directly reprogrammed neurons.